Higher education challenges to teaching practices: perspectives drawn from a multidisciplinary peer observation of teaching program - Ana Mouraz (2013)
Teachers in higher education are now, all over the world, challenged to shift their practices towards a new paradigm focused on students and their learning. However such appeals rarely take into account that changes may proceed from current didactic practices and relate with teachers3; awareness about his/her own performance. The peer review model of peer observation of teaching is seen as an important opportunity to improve teaching practices, an opportunity that can be fostered within a multidisciplinary peer observation scheme. Aiming to go deeper on the role of current practices and teachers3; awareness about their performance to improve teaching practices in higher education, some research data collected during a multi-disciplinary peer observation of teaching program are presented and discussed. It can be concluded that multidisciplinary collaboration can be a path for mutual enrichment, not only by recognizing among the other ways of doing those that can be transposed into our field, but also by recognizing weaknesses and strengths in ourselves.